PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK MENDUKUNG KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Margolang, Nurul Fadillah; Khayroiyah, Siti (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Mathematics is a science that consists of abstract concepts and considered difficult because learning is monotonous. The existence of learning media is so important to assist teachers in presenting interesting teaching materials . This study aims to produce learning media in the form of animated videos to support students' mathematical representation abilities. This research was carried out at MTs Al-Ikhlas Korajim with a Research and Development (RnD) research design using a 4D model (Define, Design, Development, Disseminate). The research instrument used was a questionnaire, media expert and material expert validation sheets, and pretest and posttest questions. Based on the results of the study, the validity results were 5.22 (very valid), 81% (very practical), and 82% (very effective) at a n-gain score of 68.94%, namely the moderate category level. So, the conclusion animated video learning media is valid, practical, and effective for supporting students' mathematical representation abilities.